CHARACTER EDUCATION VALUES IN POETRY COLLECTION DILEMA MELAYU PATANI CREATION PHAOSAN JEHWAE: NILAI-NILAI PENDIDIKAN KARAKTER DALAM KUMPULAN SAJAK DILEMA MELAYU PATANI KARYA PHAOSAN JEHWAE - Fateenee Sa-Mae; Hari Kusmanto; Ali Imron Al-Ma’ruf; Markhamah; Atiqa Sabardila (LLDIKTI Wilayah X, 2021)
This study aims to describe the values ​​of character education in the poem Phaosan Jehwae's Malay Patani Dilemma. The main approach used in this study is descriptive qualitative. The data of this research are the expressions in the Patani Malay Dilemma poetry which have character education values. The data source of this research is Phaosan Jehwae's Malay Patani Dilemma poetry. The data of this research were collected by means of documentation, observation, and note-taking techniques. This research data analysis using referential matching method. The results of this study indicate that there are eight values ​​of character education in the poems of Patani's Malay Dilemma by Phaosan Jehwae. The eight values ​​of character education include: (1) the character of love for the country, (2) religious character, (3) the character of hard work, (4) the character of optimism, (5) the character of being friendly or communicative, (6) the character of justice, (7) the character of language politeness, and (8) the character of wisdom. This shows that these poems are good for learning materials. This research is useful as a medium for character building students in high school.